N6-methyladenosine demethylases Alkbh5/Fto regulate cerebral ischemia-reperfusion injury. (April 2020) - Xu, Kaiwei; Mo, Yunchang; Li, Dan; Yu, Qimin; Wang, Lu; Lin, Feihong; Kong, Chang; Balelang, Meita Felicia; Zhang, Anqi; Chen, Sijia; Dai, Qinxue; Wang, Junlu
Background: Although N 6 -methyladenosine (m 6 A) plays a very important role in different biological processes, its function in the brain has not been fully explored. Thus, we investigated the roles of the RNA demethylases Alkbh5/Fto in cerebral ischemia-reperfusion injury. Methods: We used a rat model and primary neuronal cell culture to study the role of m 6 A and Alkbh5/Fto in the cerebral cortex ischemic penumbra after cerebral ischemia-reperfusion injury. We used Alkbh5-shRNA and Lv-Fto ( in vitro ) to regulate the expression of Alkbh5/Fto to study their regulation of m 6 A in the cerebral cortex and to study brain function after ischemia-reperfusion injury. Results: We found that RNA m 6 A levels increased consecutive to the increase of Alkbh5 expression in both the cerebral cortex of rats after middle cerebral artery occlusion, and in primary neurons after oxygen deprivation/reoxygenation. In contrast, Fto expression decreased after these perturbations. Our results suggest that knocking down Alkbh5 can aggravate neuronal damage. This is due to the demethylation of Alkbh5 and Fto, which selectively demethylate the Bcl2 transcript, preventing Bcl2 transcript degradation and enhancing Bcl2 protein expression. Conclusion: Collectively, our results demonstrate that the demethylases Alkbh5/Fto co-regulate m 6 A demethylation, which plays a crucial role in cerebral ischemia-reperfusion injury. The results provide novel insights into potential therapeutic mechanisms for stroke.